Analysis of code-mixing in the novel Antares by Rweinda: A sociolinguistics approach - Pradina Anugrah Anggraeni; Murni Fidiyanti (SULUK: Jurnal Bahasa, Sastra, dan Budaya, 2023)
Code-mixing is a phenomenon where two or more languages are combined in speech or writing. It occurs when individuals use elements from different languages within a single utterance, whether it be a word, phrase, or clause. Code-mixing is not limited to oral communication; it is also prevalent in written forms, including literary works such as novels. One of the novels that employs code-mixing is Antares by Rweinda. The characters in the novel utilize code-mixing to communicate with each other. Therefore, this study addresses two main questions: what are the types and forms of code-mixing present in the novel Antares by Rweinda. The types of code-mixing include inner and outer code-mixing, while the forms of code-mixing encompass words, phrases, and clauses. This study aims to examine and describe the types and forms of code-mixing in Rweinda's novel, Antares. This research employed a descriptive qualitative method to effectively describe the data, focusing on the main research objectives. The results indicated the presence of two types of code-mixing: six instances of inner code-mixing, including Sundanese and Javanese, and thirteen instances of outer code-mixing, such as English and Arabic. Meanwhile, in terms of form, code-mixing was observed in fourteen instances in word forms, where English words dominated. Additionally, five instances were identified in phrase form, also predominantly consisting of English words. However, no instances of code-mixing were found in clause form.